SUN PROTECTION FACTOR (SPF) VALUE AND PHYSICAL PROPERTIES OF PURIFIED GAMBIER GEL PREPARATION - Faizin, Muhammad Asrofi; Purwanto, Purwanto (Jurnal Farmasi Sains dan Praktis, 2024)
Gambier is an export product from Sumatera, Indonesia, that can be purified and utilized in cosmetic preparations. The content of phenolic and flavonoid compounds of purified gambier has a potential skin protection against UV rays. The chemical content of extract is closely related to the polarity of solvent, so this study aims to analyze the effect of ethanol concentration as solvent in gambier purification on phenolic content, flavonoids, and SPF value. The ethanol concentrations for this purpose were 0%, 25%, 50%, 75% and 96%. Total phenolic and flavonoid contents were analyzed by colorimetric method, whereas the SPF value of gel was measured by UV spectrophotometer. The gel preparation was evaluated for its physical properties including organoleptic test, spreadability, adhesiveness, viscosity, pH and stability. Statistical analysis performed with one-way ANOVA at 95% confidence level. As the results, ethanol concentration significantly influenced phenolic, flavonoid content and SPF values. The highest phenolic content was obtained in purification by 50% ethanol with a value of 757.2 ± 13.1 mg GAE/g, while highest flavonoid content was achieved in 96% ethanol at 5.18 ± 0.21 mg QE/g. Ethanol concentration with highest SPF value was 96% at 27.07 ± 0.33. In the gambier gel formulation with 0.2% dose had an SPF value of 6.60 ± 0.58. The gel has good homogeneity, viscosity, and pH for cosmetic preparations but poor spreadability. The stability of the gel formulation changed after accelerated stability testing for 4 weeks